Study on effects of damping in laminated rubber bearings on seismic responses for a 1 - Yoo, Bong (Earthquake engineering & structural dynamics.)
The effects of damping in various laminated rubber bearings (LRB) on the seismic response of a 1/8 scale isolated test structure are investigated by shaking table tests and seismic response analyses. A series of shaking table tests of the structure were performed for a fixed base design and for a base isolation design. Two different types of LRB were used : natural rubber bearings (NRB) and lead rubber bearings (LLRB). Three different designs for the LLRB were tested; each design had a different diameter of lead plug, and thus, different damping values. Artificial time histories of peak ground acceleration 0.4 g were used in both the tests and the analyses. In both shaking table tests and analyses, as expected, the acceleration responses of the seismically isolated test structure were considerably reduced. However, the shear displacement at the isolators was increased. To reduce the shear displacement in the isolators, the diameter of the lead plug in the LLRB had to be enlarged to increase isolator damping by more than 24 percent. This caused the isolator stiffness to increase, and resulted in amplifying the floor acceleration response spectra of the isolated test structure in the higher frequency ranges with a monotonic reduction of isolator shear displacement.